2021
DOI: 10.1136/bmjopen-2021-052598
|View full text |Cite
|
Sign up to set email alerts
|

Home-based rehabilitation programme compared with traditional physiotherapy for patients at risk of poor outcome after knee arthroplasty: the CORKA randomised controlled trial

Abstract: ObjectivesTo evaluate whether a home-based rehabilitation programme for people assessed as being at risk of a poor outcome after knee arthroplasty offers superior outcomes to traditional outpatient physiotherapy.DesignA prospective, single-blind, two-arm randomised controlled superiority trial.Setting14 National Health Service physiotherapy departments in the UK.Participants621 participants identified at high risk of a poor outcome after knee arthroplasty using a bespoke screening tool.InterventionsA multicomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Stratification on rehabilitation need may, therefore, be warranted. While previous authors have attempted to identify those at most risk of poor outcomes postoperative,51 52 there remains uncertainty over what physiotherapy intervention is more beneficial for these patients. Further consideration on the optimal rehabilitation programme to promote physical activity for those with the most to gain as opposed to assuming all, as adopted in this trial, may be indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Stratification on rehabilitation need may, therefore, be warranted. While previous authors have attempted to identify those at most risk of poor outcomes postoperative,51 52 there remains uncertainty over what physiotherapy intervention is more beneficial for these patients. Further consideration on the optimal rehabilitation programme to promote physical activity for those with the most to gain as opposed to assuming all, as adopted in this trial, may be indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Additional file 1: Supplementary file. SRQR Equator standards for reporting qualitative research [3].…”
Section: Supplementary Informationmentioning
confidence: 99%
“…It aimed to determine whether a home-based multi-component rehabilitation programme provided to patients deemed at risk of a poor outcome following knee arthroplasty using a bespoke screening tool was better than usual out-patient based care. The CORKA trial rehabilitation package was delivered by physiotherapy assistants with supervision from qualified physiotherapists [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…erefore, the proposed study on victims with acute myocardial infarction PCI postoperative stage II remote home rehabilitation, compared with old style casualty rehabilitation efficacy [5], hope by the aid of remote ECG detection technology [6], real-time, and incessant intensive caring of the patient's health auxiliary PCI postoperative patients having acute myocardial infarction, the guidance of doctors treatment outside the hospital rehabilitation treatment and health management for a long time to make the rehabilitation management and follow-up of AMI patients precise and standardized [7], so as to improve patient compliance, further improve the continuity of AMI patients' diagnosis and treatment in and out of the hospital, reduce patients' rehospitalization rate and mortality, and improve the worth of life.…”
Section: Introductionmentioning
confidence: 99%